Functional and immunohistochemical characterization of CCEae3a, a carboxylesterase associated with temephos resistance in the major arbovirus vectors Aedes aegypti and Ae. albopictus. (July 2016) - Grigoraki, Linda; Balabanidou, Vassileia; Meristoudis, Christos; Miridakis, Antonis; Ranson, Hilary; Swevers, Luc; Vontas, John
Abstract: Temephos is a major organophosphate (OP) larvicide that has been used extensively for the control of Aedes albopictus and Aedes aegypti, the major vectors for viral diseases, such as dengue fever, zika and chikungunya. Resistance to temephos has been recently detected and associated with the upregulation of carboxylesterases (CCEs) through gene amplification, in both species. Here, we expressed the CCEae3a genes which showed the most striking up-regulation in resistant Aedes strains, using the baculovirus system. All CCEae3a variants encoded functional enzymes, with high activity and preference for p-nitrophenyl butyrate, a substrate that was shown capable to differentiate temephos resistant from susceptible Aedes larvae. Enzyme kinetic studies showed that CCEae3as from both Ae. aegypti and Ae. albopictus (CCEae3a_aeg and CCEae3a_alb, respectively) strongly interact with temephos oxon and slowly released the OP molecule, indicating a sequestration resistance mechanism. No difference was detected between resistant and susceptible CCEae3a_aeg variants (CCEae3a_aegR and CCEae3a_aegS, respectively), indicating that previously reported polymorphism is unlikely to play a role in temephos resistance. HPLC/MS showed that CCEae3as were able to metabolize temephos oxon to the temephos monoester [(4-hydroxyphenyl) sulfanyl] phenyl O, O-dimethylphosphorothioate. Western blot and immunolocalization studies, based on a specific antibody raised against the CCEae3a_alb showed that the enzyme is expressed at higher levels in resistant insects, primarily in malpighian tubules (MT) and nerve tissues. Graphical abstract: Highlights: Carboxyesterases (CCEs) from Aedes vectors associated with temephos resistance were functionally expressed. Enzyme kinetic analysis showed that CCEae3as strongly interact with temephos oxon. HPLC/MS analysis showed that CCEae3as metabolize temephos oxon to a temephos monoester. Western and immunolocalization studies showed that CCEae3a_alb is localized in malpigian tubules and the nervous system.